Posteromedial Translation for Correction of Severe Hypokyphosis in Adolescent Idiopathic Scoliosis: Outcome Analysis with 2-year Follow-ups - Mirzashahi, Babak; Dehghani Firoozabadi, Mohammad Javad; Rostami, Mohsen; Panahi, Saeed; Talebiyan, Parham; Yaseen Khan, Furqan Mohammed (Archives of neuroscience, 2023)
Background: The deformity in the coronal plane is over-emphasized in the surgical management of adolescent idiopathic scoliosis (AIS), whereas the importance of the patient’s sagittal profile is generally neglected. Gold standard treatment in AIS consists of posterior instrumentation, deformity correction - through a reduction maneuver - and arthrodesis. The main focus in most reduction techniques is placed on the correction of deformity in the coronal and/or axial plane, worsening the patient’s sagittal profile. Objectives: This outcome analysis study aimed to investigate the surgical treatment of AIS patients with severe thoracic hypokyphosis (< 10) by adopting the posteromedial translation technique (PMT). Methods: In this retrospective study, the data and records of the patients with minimum 2-year follow-ups were analyzed. Correction of the deformity was radiologically assessed based on Cobb’s angle, thoracic kyphosis, and apex translation. The Scoliosis Research Society 22-item questionnaire (SRS-22r) was used for clinical evaluation before and after the surgery. Results: A total of 11 AIS patients (8 females and 3 males) with hypokyphosis underwent operations by the PMT at Imam Khomeini Hospital Complex between 2000 and 2020. According to the results, 78% correction in the coronal plane and an average correction of 56° (P < 0.001) were obtained. As for the sagittal plane, 18.8° correction was recorded (75%) (P < 0.001). Scoliosis Research Society 22-item questionnaire subscale analysis showed a significant improvement in patients' self-image (P = 0.035) and satisfaction (P = 0.043). Conclusions: The management of hypokyphosis in AIS was challenging. The PMT facilitated the tri-planar deformity correction, including a restoration of the thoracic kyphosis in all patients. A significant improvement was observed in both the coronal and sagittal profiles of the patients.